Aberrant CD8+T cells drive reproductive dysfunction in female mice with elevated IFN-γ levels - Bafor, Enitome E.; Erwin-Cohen, Rebecca A.; Martin, Toni; Baker, Clayton; Kimmel, Adrienne E.; Duverger, Olivier; Fenimore, John M.; Ramba, Meredith; Spindel, Thea; Hess, Megan M.; Sanford, Michael; Lazarevic, Vanja; et al. (Frontiers in Immunology, 2024)
Interferon-gamma (IFN-γ) is pivotal in orchestrating immune responses during healthy pregnancy. However, its dysregulation, often due to autoimmunity, infections, or chronic inflammatory conditions, is implicated in adverse reproductive outcomes such as pregnancy failure or infertility. Additionally, the underlying immunological mechanisms remain elusive. Here, we explore the impact of systemic IFN-γ elevation on cytotoxic T cell responses in female reproduction utilizing a systemic lupus-prone mouse model with impaired IFN-γ degradation. Our findings reveal that heightened IFN-γ levels triggered the infiltration of CD8+T cells in the pituitary gland and female reproductive tract (FRT), resulting in prolactin deficiency and subsequent infertility. Furthermore, we demonstrate that chronic IFN-γ elevation increases effector memory CD8+T cells in the murine ovary and uterus. These insights broaden our understanding of the role of elevated IFN-γ in female reproductive dysfunction and suggest CD8+T cells as potential immunotherapeutic targets in female reproductive disorders associated with chronic systemic IFN-γ elevation.